Clean and Healthy Living Behavior Education and Anthropometric Examination at Kindergarten/Elementary School of Tunas Sebernaman - Harahap, Azra Wifa Ilham; Purnama, Bena Melinda; Sianipar, Tasya Amanda; Rasyid, Teuku Rifqi Harun Al; Liza Lubis, Humairah Medina (Kontribusia : Research Dissemination for Community Development, 2025)
Efforts to improve public health must begin at an early age to build and realize a better environmental health status, by creating awareness, ability, and habit of applying clean and healthy living behavior. Efforts are needed by educating from an early age to get used to clean and healthy living behavior, one of the efforts is to educate in the school environment, related to clean and healthy living behavior the school environment is the first step to empowering students, teachers, and the community living in the school environment to be able to carry out clean and healthy living behavior in realizing a clean and healthy school environment. The Real Work Lecture (KKN) program was carried out in Deli-Serdang Regency, Kutalimbaru District, Pasar X Village, Hamlet I at Kindergarten / Elementary School of Tunas Sebernaman, we agreed with the principal and teaching staff at the elementary school to carry out two real work lecture programs, namely health education related to clean and healthy living behavior and anthropometric examination of students of Kindergarten / Elementary School Tunas Sebernaman as for the series of activities in the form of pre-tests, exposure to clean and healthy living behavior material, anthropometric examination, post-test. The location of the KKN program at Tunas Sebernaman Tunas Sebernaman.